Hematologic and Biochemical Reference Interval Development and the Effect of Age, Sex, Season, and Location on Hematologic Analyte Concentrations in Critically Endangered Yangtze Finless Porpoise (Neophocaena asiaeorientalis ssp. asiaeorientalis) - Nabi, Ghulam; Robeck, Todd R.; Hao, Yujiang; Wang, Ding (Frontiers in Physiology, 2019)
In this study, references intervals for 49 clinicopathological parameters were established for the critically endangered Yangtze finless porpoises (Neophocaena phocaenoides asiaorientalis). Both from the wild (Poyang Lake) and seminatural (Tian-E-Zhou Oxbow) populations, individual blood samples from 188 animals were collected from 2009 to 2017, and 2002 to 2015 respectively. For reference interval determination, we used a non-parametric bootstrap-based procedure to determine the 95th percentiles and the associated 90% confidence interval for each analyte. Our results indicated a need to partition the analyte concentrations by sex, age group or pregnancy, however, we did not find a need to partition results by location. We then used a linear mixed model to determine if evidence existed for mean differences between location with sex and season as covariates and age group as the clustered random variable on mean hematological parameters in the YFP. We found that 88% of the analytes were significant different between locations. Within the covariates, sex and season showed 31 and 69% significant difference in mean distributions, respectively. Additionally, age group provided a significant source of variation in 25% of the analytes. In summary, our finding suggests that analytes should be grouped according to sex, age, and reproductive status (non-pregnant non-lactating, pregnant and lactating). Furthermore, we have provided the first set of reference intervals for 49 clinicopathological parameters that could provide guidelines for the initial evaluation of individuals during health assessments.